How Nurses Perceived Their Work-Environments and Its Related Nursing Management Perspectives during the COVID-19 Pandemic: An Investigatory Study - Elsa Vitale (Psych, 2022)
Human resource management could be defined as the set of policies which, if properly designed and developed, contribute to improving the performance of employers. The present study aimed to investigate how nurses directly involved in the care of COVID-19 patients perceived their working activities and environments during the pandemic and if there were any associations between their perceptions’ levels and sampling characteristics. An observational, multicenter, cross- sectional study was carried out from October 2021 to February 2022. Socio-demographic characteristics and a total of 10 items were collected in order to assess nurses’ perceptions on their working activities and environments during the pandemic. A total of 126 nurses were recruited in this study. Of these, 35 (27.8%) were males and 91 (72.2%) were females. The most part of participants (62.7%) aged between 20–30 years and were employed during their first decade of work experience (69.8%), were employed only during the morning (46%) and attended the basic nursing course (82.5%). Most of participants considered their nursing activities as very hard, in both the age and work experience groups. Additionally, further associations were reported between nurses who were employed during the three shifts par day, as they considered their activities very hard; however, data were higher in one/shift group than in the three-shift group, too. Younger nurses reported higher emotional levels in their nursing activities than their older collogues (11–20 years and 21–30 years), while the oldest group recorded higher levels of emotional involvement than the younger groups (11–20 years and 21–30 years), respectively. Finally, all groups of work experience nurses considered the nursing activities very hard. The perceived organization work environment was not favorable, explaining potential opportunities for intervention by also improving nurses’ well-being, particularly during this very hard period of the pandemic. Therefore, nursing leaders might influence the orientation and development of collaborators by involving them with respect to the choices and challenges of the administration, rather than traditional managers who interpreted their role through complicated command procedures and control.